Innovative management and business practices in Asia - Ordóñez de Pablos, Patricia, 1975-; Zhang, Xi, 1982-; Chui, Kwok Tai, 1991- (Advances in human resources management and organizational development (AHRMOD) book series., 2020)
""This book contains research that enhances understanding and collaboration in business, management, and technology in Asia for the present and in the future"--Provided by publisher"--